Suzuki reactions of aryl halides with phenylboronic acid using imidazolium-based ionic liquid as a green solvent under microwave irradiation - Son Nam, Phan Thanh; Thanh, Truong Vu; Duy Hien, Nguyen Thi; Nguyet, Vo Thi (Vietnam Journal of Chemistry, 2014)
An easily accessible ionic liquid, 1-hexyl-3-methylimidazolium bromide, was synthesized from n-hexyl bromide and N-methylimidazole under microwave irradiation condition, and characterized by 1H and 13C NMR, and MS. The ionic liquid was demonstrated to be an efficient and recyclable solvent for the Suzuki cross-coupling reaction between several aryl halides and phenylboronic acid under microwave irradiation to form biphenyls as the principal products. The most commonly used base in several Suzuki reactions, Na2CO3, was found to be significantly less effective than triethylamine for the reaction carried out in the ionic liquid. Using the ionic liquid as the reaction solvent in conjunction with microwave irradiation, the reaction rate was dramatically enhanced, with 99% conversion being achieved within 2 minutes, while less than 5% conversion was observed after 8 hours for the reaction under conventional heating condition. Furthermore, the ionic liquid could be reused without significant degradation in activity.